Facultative and persistent offspring sex-ratio bias in relation to the social environment in cooperatively breeding red-winged fairy-wrens (Malurus elegans) - Pot, Morrison T.; Brouwer, Lyanne (Behavioral ecology and sociobiology, 2022)
Females should facultatively bias offspring sex ratio when fitness returns vary among sexes. In cooperative breeders, where individuals help raise others’ young, overproducing the philopatric sex will be adaptive when helpers are absent, whereas overproducing the dispersive sex may be adaptive to reduce intrasexual competition. Thus, fitness returns are expected to vary with the social environment. However, any offspring sex-ratio biases may also result from consistent among-female differences (e.g. quality) and/or environmental variables (e.g. food availability). Yet, few studies have disentangled facultative from persistent biases. We investigated offspring sex-ratio biases in relation to the social environment in cooperatively breeding red-winged fairy-wrens ( Malurus elegans ). Repeated observations of the same females over nine years allowed for disentanglement of facultative from persistent biases. Females without help did not overproduce daughters, despite female helpers being associated with higher fledgling survival (resource enhancement hypothesis). Instead, females without helpers facultatively overproduced sons —the slower dispersing sex— thereby ensuring long-term helper availability. Furthermore, offspring sex ratio was not biased towards the rarer sex of helpers present in the group or population (resource competition hypothesis). However, females with sex-biased helping produced similarly skewed offspring sex ratios. This among-female association may not be surprising, because helpers are previous seasons’ offspring. Thus, in addition to facultative responses to prevailing social conditions, we found evidence for persistent biases among females. This could potentially explain previous evidence for resource competition/enhancement that have typically been interpreted as facultative responses, highlighting the need for a within-female approach to better understand the adaptiveness of sex-ratio biases. Significance statement Under certain conditions, females may benefit from producing a biased offspring sex ratio, but evidence for such effects in vertebrates is weak and inconsistent. Here, using observations of the same females under different social conditions, we show that cooperatively breeding red-winged fairy-wrens facultatively biased offspring sex ratio towards sons when living in pairs, thereby ensuring the availability of a workforce to assist in raising future offspring. However, biased offspring sex ratio patterns may also be the result of consistent differences among females. Indeed, we also found evidence for such patterns and suggest that this could be an explanation for previous findings which are often interpreted as facultative responses.